PENGEMBANGAN SISTEM PENCATATAN KELAHIRAN DAN KEMATIAN BERBASIS SELULER - Muarrikh Yazka Ginang Prasidana; Nori Wilantika (Seminar Nasional Official Statistics, 2020)
Demand for population data at Indonesia Central Bureau of Statistics (BPS) is quite high, reaching 35.55% of the total data requests for social statistics. Birth and death data are the main part of population data as a basis for planning development. Almost all sectors and agencies require data on births and deaths. Data on births and deaths can be obtained from census and survey results conducted by BPS or from population administrative data. However, the data from census and survey have a drawback. The data do not describe the current state due to the time span between census and survey is too long and the process from enumeration to dissemination is also long. Population administrative data also has shortcomings. The current system requires people to be active in reporting various important population events that occur in their family environment whom not all are active and disciplined to report. Based on these problems, this study aims to build a system that can record births and deaths without waiting for a time span of 5 or even 10 years and without waiting for the public to report the incident. The birth and death registration system is designed to be implemented online and integrated in health facilities where almost births and deaths occur and are located in almost all sub-districts in Indonesia. The development of this system uses the Waterfall Model method, resulting in two subsystems which are a mobile application with 9 functions and a monitoring website with 5 functions. The test results of the system show that all functions can work well, are acceptable to users, and can solve the problems of current birth and death registration.